3D Interactive Visualization Scenario to Improve Public Participation in the Visual Comfort Assessment for the Pedestrian in Provincial Street, Malang, Indonesia. (December 2018) - Santosa, Herry; Ernawati, Jenny; Wulandari, Lisa Dwi
Abstract: The visual comfort of pedestrians in the street corridor is essential to encourage a continuously satisfying experience of a visual aesthetic leading to a better quality of urban spaces, which is significant for making cityscape, especially in the streetscape. Valuable visual attributes of the pedestrian spaces are indicated by the presence of visual comfort for pedestrians as they pass through the pedestrian space. The creation of visual comfort in the pedestrian spaces also encourages positive spaces along the road corridor, generating an excellent space utilization, which eventually led to many positive appreciations of the space environment.Creating high-quality urban places triggers a more sustainable urban development by increasing pedestrian satisfaction in visual comfort through empowering public engagement in online decision-making system. Thus, public participatory is urgently needed to evaluate the spatial and visual comfort of provincial streetscapes. The disturbance of visual comfort for pedestrians often occurs in the main road corridors, especially the provincial streets in Malang, which has a strategic location for the expansion of commercial functions. This study evaluated a visual comfort of pedestrians in the provincial streets. It employed the 3D modeling method combined with the interactive simulation through the use of a multimedia authoring platform software to develop the 3D Interactive Visualization Scenario for online participation. The result of this study was the scenario of 3D visualization interactivity development to improve the effectiveness of the decision-making system in the assessment of pedestrian visual comfortalong the provincial street corridor.